Enhancing Policyholder Experience Through Cloud-Based IoT Integration - Shikha Gurjar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This technical exploration examines how Internet of Things (IoT) technology combined with cloud computing transforms the insurance industry. The integration enables insurers to collect, process, and analyze data from connected devices to improve risk assessment, customer engagement, and policy design. The document details a multi-layered architecture comprising the device, gateway, cloud processing, and application layers that form the foundation for IoT insurance implementations. It explores specific applications in auto insurance telematics and property insurance, addressing data processing pipelines, security considerations, integration with core systems, and performance optimization techniques. The document also provides a case study of a comprehensive IoT insurance platform and examines future technical directions, including digital twins, federated machine learning, blockchain integration, and quantum-resistant cryptography.
Keywords: IoT insurance; cloud architecture; telematics; smart home integration; edge computing